2014
DOI: 10.1039/c3lc51247a
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular-controlled breast cancer cell formation and growth using non-UV patterned hydrogels via optically-induced electrokinetics

Abstract: The culturing of cancer cells on micropatterned substrates can provide insight into the factors of the extracellular environment that enable the control of cell growth. We report here a novel non-UV-based technique to quickly micropattern a poly-(ethylene) glycol diacrylate (PEGDA)-based hydrogel on top of modified glass substrates, which were then used to control the growth patterns of breast cancer cells. Previously, the fabrication of micropatterned substrates required relatively complicated steps, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
0
37
0
2
Order By: Relevance
“…Requiring only visible light projection images, this technique provides potentially a low-cost and high throughput process to "print" micro polymer structures. We have demonstrated that this fabrication technique has a lateral-resolution of 3 μm (a limitation of the pixels of the optical projection system), which is sufficient for single cell studies [41]. In terms of vertical-resolution, the thickness of fabricated hydrogel structures range from tens of nanometers to hundreds of micrometers; and hence, this technology could potentially be applied for substrate surface modification and three-dimensional tissue scaffold research.…”
Section: Discussionmentioning
confidence: 99%
“…Requiring only visible light projection images, this technique provides potentially a low-cost and high throughput process to "print" micro polymer structures. We have demonstrated that this fabrication technique has a lateral-resolution of 3 μm (a limitation of the pixels of the optical projection system), which is sufficient for single cell studies [41]. In terms of vertical-resolution, the thickness of fabricated hydrogel structures range from tens of nanometers to hundreds of micrometers; and hence, this technology could potentially be applied for substrate surface modification and three-dimensional tissue scaffold research.…”
Section: Discussionmentioning
confidence: 99%
“…OEK, essentially a dielectrophoresis (DEP) system, uses digitally and optically projected images to define virtual electrodes instead of metal electrodes. Transport, 11 separation, 12,13 rotation, 14,15 and patterning 16 of micro/nanoparticles, including cells and DNAs, are major features of OEK technology. We have recently developed an OEK-based method capable of measuring the mass and density of a single bead and yeast cell.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our proposed assay system provided high compatibility with conventional glass-based microarray formats thanks to the optical method for active mass transport, resulting in improved reaction efficiency with minimal sample consumption (5 ll). Based on these technological attractions, the proposed optoelectrofluidic immunoassay system is considered as one of the potential candidates to develop optically controlled micro total analysis systems (lTAS) for biological fields such as protein expression study and diagnostics by integrating various versatile manipulation methods for cells, 30 biomolecules, 31 and micro-and nano-sized particles 32 of optoelectrofluidic technologies.…”
Section: Resultsmentioning
confidence: 99%